Obtenção e caracterização estrutural, microestrutural e elétrica do condutor protônico BaCe1-xYxO3-δ com e sem aditivo de sinterização - Pires, Elcio Liberato (2016)
The study of solid electrolytes (SE) is important to the scientific and technological development of materials used in application related to clean energy generation, such as Solid Oxide Fuel Cells (SOFCs). Yttrium-doped Barium Cerate is a SE with perovskite structure and great potential for this application because of its high values of protonic conductivity in temperatures between 350 and 600°C, which would allow the replacement of the currently used Zirconia based SE that operate above 800 °C, reducing the manufacturing cost of SOFCs. In the present work, eighteen compositions of BaCe1-xYxO3-δ system with x ranging from 0 to 0.2 were synthesized via modified citrate process and for half of the compositions an addition of 1 wt% ZnO as sintering aid was made. With the goal of establishing a correlation between structure, microstructure and electrical conductivity with the yttrium concentration and in the presence or absence of the sintering aid, all compositions were characterized with X-ray Powder Diffraction, Raman Spectroscopy, Scanning and Transmission Electron Microscopy (TEM), Energy-dispersive X-ray Spectroscopy (EDS) and Impedance Spectroscopy. Secondary phases were characterized using TEM, EDS and Electron Diffraction. All samples presented relative bulk density values above 95%. The bulk electrical conductivity is proportional to the yttrium concentration in the grain and, in general, the ZnO addition promoted grain growth, increasing its average size up to five times in some compositions. The ZnO acts mainly at the grain boundary region and it is effective as sintering aid only when the composition has some yttrium content. Among all synthesized compositions, BaCe0.8Y0.2O3-δ without ZnO addition showed the highest electrical conductivity value at 600°C (≈ 31.5 mS/cm). In the group of samples with ZnO, the highest values (close to 18.4 mS/cm), were obtained for compositions with Yttrium content above 14 at.%.